Phytochemical Composition, Antioxidant Activity, and Bioactive Compound Profiling of Sargassum sp. Ethanol Extract: Potential for Antimalarial Application - Eka Sulistianingsih; Misbahul Huda; Endah Setyaningrum; Budi Setiawan (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
Sargassum sp., a brown macroalga abundant in Indonesia's coastal ecosystems, has garnered attention for its diverse bioactive compounds with pharmacological potential. However, its application as a natural antimalarial and antioxidant agent remains underexplored. This study aimed to investigate the secondary metabolites in ethanol extracts of Sargassum sp. and evaluate their antioxidant and potential antimalarial activities. Ethanol extraction was conducted using the maceration technique, followed by phytochemical screening, FT-IR, and GC-MS analyses to characterize the extract. The results revealed the presence of saponins, terpenoids, tannins, alkaloids, and flavonoids. FT-IR and GC-MS confirmed compounds associated with antioxidant and antimalarial properties. The extract exhibited notable antioxidant activity with an IC₅₀ value of 26.16 ppm. These findings highlight the potential of ethanol-extracted Sargassum sp. as a promising source for the development of safer, resistance-limiting antimalarial and antioxidant agents.